Strategi Pencegahan Stunting Melalui Edukasi MPASI di Kelurahan Tanah Baru, Kecamatan Bogor Utara, Kota Bogor - Solahuddin, Radithya Annaafi; Fitriani, Dindana; Anggarani, Putri; Magdalena, Lay Agnes; Hasibuan, Nia Julianti; Munawaroh; Putra, Elnatasra Athilla Selananda; Khairani, Dini; Fahry, Rheyhan; Pratiwi, Prita Indah (Jurnal Pusat Inovasi Masyarakat, 2024)
Stunting is a long-term nutritional issue arising from prolonged inadequate dietary ingestion. Stunting can begin during fetal development and typically becomes evident when a child reaches two years of age. It represents a critical health system concern, as it reflects impaired growth in young children due to chronic malnutrition and recurrent infections. This program aims to reduce the risk of stunting by enhancing awareness, behaviors, and habits regarding food intake and complementary feeding (MPASI). The program is one of the initiatives organized by the KKN (student community services program) IPB group in Tanah Baru Sub-district, Bogor Utara District, Bogor City. The program consisted of the participation in health services at the Posyandu, including anthropometric measurements for infants and toddlers, and the educational campaign on stunting prevention through MPASI. The activities were conducted at Posyandu Cempaka B, Tanah Baru, with a total of 24 participants, including mothers of infants and toddlers, women of childbearing age, and health cadres. The socialization program was conducted in a hybrid format, featuring expert speaker in the field of nutrition. Educational materials included presentation slides, MPASI recipe videos, recipe book, and examples of balanced and nutritious MPASI. The activities was succeed, marked by high participant enthusiasm, as demonstrated by their active engagement throughout the program and their eagerness to ask questions and consult with the experts. This program is expected to improve awareness of the importance of fulfilling nutritional needs during early childhood, thereby contributing to stunting prevention in the area.